Lightweight Cryptography for Internet of Things: A Review - Amrita; Ekwueme, Chika Paul; Adam, Ibrahim Hussaini; Dwivedi, Avinash (EAI Endorsed Transactions on Internet of Things, 2024)
The paper examines the rising significance of security in Internet of Things (IoT) applications and emphasizes the need for lightweight cryptographic solutions to protect IoT devices. It acknowledges the growing prevalence of IoT in various fields, where sensors collect data, and computational systems process it for action by actuators. Due to IoT devices’ resource limitations and networked nature, security is a concern. The article compares different lightweight cryptographic block cipher algorithms to determine the best approach for securing IoT devices. It also discusses the merits of hardware versus software solutions and explores potential security threats, including intrusion and manipulation. Additionally, the article outlines future work involving the implementation of the trusted Advanced Standard Encryption block cipher in IoT devices, including its use in quick-response (QR) code scanning and messaging platforms. It acknowledges existing drawbacks and suggests areas for improvement in IoT system performance and security.